Base film, method for producing the same, composite current collector, electrode sheet, and electrochemical device
Patent Information
- Application Number
- CN202611158595.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]复合集流体核心性能为界面结合力、基材机械强度、电解液稳定性,当前单一高分子基材均存在性能短板,膜界面结合力弱是规模化量产与长效应用的核心瓶颈
本发明提供的基膜,其表层包含构成分散相的聚合物和构成连续相的聚合物,通过限定构成分散相的聚合物的结晶终止温度低于构成连续相的聚合物的结晶起始温度,使两相聚合物的结晶温度区间互不重叠,由此在材料层面构建了具有结晶温度梯度差异的两相共混体系。上述时序化分级结晶机制消除了传统共混体系因两相结晶温度区间重叠所导致的结晶竞争、晶粒粗化及内应力集中问题,使基膜内部形成晶粒排布均匀、缺陷密度低、内应力分布均匀的结晶结构,从而实现了基膜抗拉强度与断裂伸长率的协同提升。
Smart Images

Figure CN123017982A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery current collector technology, and in particular to a base film, its preparation method, composite current collector, electrode, and electrochemical device. Background Technology
[0002] Composite current collectors are core materials for lithium batteries, employing a "metal-polymer substrate-metal" sandwich structure and manufactured by double-sided copper / aluminum plating on PET, PP, or PI films. They offer advantages such as lightweight design, puncture resistance, and low short-circuit risk, making them suitable for the high safety requirements of power batteries and energy storage batteries, and can replace traditional metal foils.
[0003] The core performance characteristics of composite current collectors are interfacial adhesion, substrate mechanical strength, and electrolyte stability. Currently, all single polymer substrates have performance shortcomings, with weak interfacial adhesion being a key bottleneck for large-scale mass production and long-term application. The three main substrates each have their drawbacks: PET has excellent industrial compatibility and mechanical properties, but poor resistance to electrolyte corrosion, leading to coating peeling during long-term cycling, resulting in increased battery internal resistance, capacity decay, and shortened lifespan; PI has excellent corrosion resistance, temperature resistance, and interfacial stability, but its high cost prevents mass production and widespread adoption; PP has low cost and electrolyte resistance, but weak surface polarity, poor compatibility with metals, and extremely low native adhesion, making direct coating processing impossible.
[0004] Existing surface modification processes in the industry are merely remedial measures, addressing the symptoms but not the root cause: corona treatment and plasma activation can only temporarily improve surface activity, with effects easily diminishing, and the finished product still faces the risk of coating peeling off; acrylic primers can enhance adhesion, but mass production consistency is poor, and the coating's resistance to electrolytes is insufficient, leading to swelling and failure with long-term use, failing to achieve long-term coating adhesion. Simultaneously, existing substrates and conventional blended substrates lack sufficient rigidity and toughness, resulting in low tensile strength and elongation at break of the finished product. In downstream cell coating, rolling, and slitting processes, substrate breakage and coating cracking and peeling are prone to occur, leading to decreased production yield and increased risk of battery short circuits.
[0005] Current industry technologies primarily rely on back-end modification and remediation, failing to address the substrate selection dilemma at the source of polymer crystallization. Conventional two-phase blended base films exhibit overlapping crystallization zones, resulting in disordered crystallization, high internal stress, and a lack of anchoring structures, further amplifying issues such as coating detachment and insufficient mechanical properties. The industry urgently needs to develop differentiated crystallization-controlled two-phase blended base film technology to achieve a low-cost, integrated balance of high interfacial adhesion, electrolyte resistance, and high mechanical properties.
[0006] In view of this, the present invention is proposed. Summary of the Invention
[0007] One of the objectives of this invention is to provide a base film that at least solves one of the technical problems existing in the prior art.
[0008] The second objective of this invention is to provide a method for preparing a base film.
[0009] A third objective of this invention is to provide a composite current collector.
[0010] The fourth objective of this invention is to provide an electrode sheet.
[0011] The fifth objective of this invention is to provide an electrochemical device.
[0012] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a base film comprising at least a first surface layer and a second surface layer, wherein the first surface layer and the second surface layer each independently comprise at least a polymer constituting a dispersed phase and a polymer constituting a continuous phase; Wherein, the polymer constituting the continuous phase at least partially encapsulates the polymer constituting the dispersed phase; the crystallization termination temperature of the polymer constituting the dispersed phase is lower than the crystallization initiation temperature of the polymer constituting the continuous phase; the preparation of the base film includes a casting process, and during the casting process, the polymer constituting the dispersed phase crystallizes at least partially before the polymer constituting the continuous phase.
[0013] Furthermore, in both the first and second surface layers, the mass ratio of the polymer constituting the dispersed phase to the polymer constituting the continuous phase is independently 1:(1-9); and / or, The thickness of the base film is 2μm-15μm.
[0014] Furthermore, in the first and second surface layers, the difference between the crystallization initiation temperature of the polymer constituting the continuous phase and the crystallization termination temperature of the polymer constituting the dispersed phase is ≥5°C, preferably ≥20°C; and / or, In the first and second surface layers, the crystalline particle size of the polymer constituting the dispersed phase is ≤5μm, preferably ≤500 nm.
[0015] Furthermore, based on 100% by mass, the first and second surface layers each independently comprise 10%-45% of the polymer constituting the dispersed phase and 50%-85% of the polymer constituting the continuous phase.
[0016] Furthermore, the polymer constituting the dispersed phase and the polymer constituting the continuous phase are selected from one of the following combinations: PET / PE, PEN / PBT, PET / PBT, PTT / PBT, PPS / PBT, PBT / PE, PET / PP, PP / PE, PA / PE, PBT / POE, PEN / PP, PBT / PP, PPS / PP, PLA / PVC, PEN / PE, PPS / PE, PPS / PBT, PTT / PBT, PEEK / PA12, PEEK / PVDF, PPS / PA6 or PPS / fluoroplastics; and / or, Based on 100% by weight, the first surface layer and the second surface layer also independently include 1%-5% compatibilizer; Optionally, the compatibilizer includes maleic anhydride-grafted polyolefins, preferably including at least one of maleic anhydride-grafted polypropylene, maleic anhydride-grafted polyethylene, and maleic anhydride-grafted polyolefin elastomers.
[0017] In a second aspect, the present invention provides a method for preparing a base film, characterized in that it includes: (A) The polymer constituting the dispersed phase of the first surface layer is mixed with the polymer constituting the continuous phase and then melted to obtain the melt of the first surface layer; (B) The polymer constituting the dispersed phase of the second surface layer is mixed with the polymer constituting the continuous phase and then melted to obtain the melt of the second surface layer; (C) The melt including the first surface layer and the melt including the second surface layer are co-extruded and then subjected to casting and stretching processes to obtain the base film; In the casting process, the crystallization of the polymer constituting the dispersed phase and the crystallization of the polymer constituting the continuous phase are carried out sequentially. The casting process includes: (a) Cooling to the crystallization temperature range of the polymer constituting the dispersed phase, so that the polymer constituting the dispersed phase is at least partially crystallized; (b) Heating to the crystallization temperature range of the polymer constituting the continuous phase, causing the polymer constituting the continuous phase to crystallize; (c) Cooling to the crystallization temperature range of the polymer constituting the dispersed phase, allowing the polymer constituting the dispersed phase to fully crystallize. Further, the preparation method satisfies one or more of the following conditions: (1) In step (a), the cooling rate is 50℃ / min-100℃ / min, and the temperature is kept constant for 30s-120s within the crystallization temperature range of the polymer constituting the dispersed phase. (2) In step (b), the heating rate is 10℃ / min-30℃ / min, and after heating, the temperature is kept constant for 60s-600s within the crystallization temperature range of the polymer constituting the continuous phase. (3) In step (c), the cooling rate is 5℃ / min-30℃ / min, and after cooling, the temperature is kept constant for 30s-120s within the crystallization temperature range of the polymer constituting the dispersed phase.
[0018] Thirdly, the present invention provides a composite current collector, wherein the composite current collector comprises the base film described above or the base film prepared by the preparation method described above.
[0019] Fourthly, the present invention provides an electrode sheet comprising the aforementioned composite current collector.
[0020] Fifthly, the present invention provides an electrochemical device, the electrochemical device comprising the aforementioned electrode.
[0021] Compared with the prior art, the present invention has the following beneficial effects: The base film provided by this invention comprises a polymer constituting a dispersed phase and a polymer constituting a continuous phase on its surface. By limiting the crystallization termination temperature of the polymer constituting the dispersed phase to be lower than the crystallization initiation temperature of the polymer constituting the continuous phase, the crystallization temperature ranges of the two polymer phases do not overlap, thereby constructing a two-phase blend system with a difference in crystallization temperature gradient at the material level. The aforementioned sequential hierarchical crystallization mechanism eliminates the problems of crystallization competition, grain coarsening, and internal stress concentration caused by the overlap of the crystallization temperature ranges of the two phases in traditional blend systems. This results in a crystalline structure with uniform grain arrangement, low defect density, and uniform internal stress distribution within the base film, thereby achieving a synergistic improvement in the tensile strength and elongation at break of the base film.
[0022] In this invention, during the cooling process of the melt blend of the two-phase polymers to form a cast film, the dispersed phase, with a lower crystallization termination temperature, preferentially crystallizes to form a uniformly dispersed microcrystalline structure. The continuous phase, with a higher crystallization initiation temperature, then crystallizes to form a complete, continuous, rigid framework. This crystallization sequence allows the dispersed phase microcrystals to be uniformly embedded within the continuous phase matrix, forming a sea-island type interpenetrating network structure with the continuous phase as the matrix and the dispersed phase as the dispersion domain. This also causes the surface of the base film to spontaneously form a uniform, uneven crystalline morphology, creating an effective mechanical interlocking structure with the metal coating and significantly improving the interfacial bonding strength between the metal coating and the base film. Furthermore, the dense grain boundaries formed by this sequential, hierarchical crystallization effectively hinder the diffusion path of electrolyte molecules within the base film, ensuring the base film maintains structural integrity and stable mechanical properties over long-term aging under electrolyte immersion conditions. Attached Figure Description
[0023] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0024] Figure 1 A flowchart illustrating the preparation process of the base film provided by this invention. Detailed Implementation
[0025] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.
[0026] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0027] A first aspect of the present invention provides a base film comprising at least a first surface layer and a second surface layer, each of the first surface layer and the second surface layer independently comprising at least a polymer constituting a dispersed phase and a polymer constituting a continuous phase; wherein the polymer constituting the continuous phase at least partially encapsulates the polymer constituting the dispersed phase; the crystallization termination temperature of the polymer constituting the dispersed phase is lower than the crystallization initiation temperature of the polymer constituting the continuous phase; the preparation of the base film includes a casting process, wherein during the casting process, the polymer constituting the dispersed phase crystallizes at least partially prior to the polymer constituting the continuous phase.
[0028] The inventors discovered that if the temperature of the two-phase melt blend is gradually reduced during casting, allowing the continuous phase to crystallize before the dispersed phase, the resulting crystal structure exhibits a smooth and dense surface after the continuous phase crystallizes. Subsequently, when the dispersed phase crystallizes on the surface, it is limited by the hardened interface of the continuous phase, forming only weak protrusions with insufficient embedding depth. This structure is prone to debonding due to interfacial shear forces when the coating is subjected to stress. Furthermore, the overlapping crystallization temperature ranges of the two phases may lead to crystallization competition, grain coarsening, and internal stress concentration issues in the two-phase blend system during crystallization.
[0029] Therefore, the present invention provides a base film whose surface layer limits the crystallization termination temperature of the polymer constituting the dispersed phase to be lower than the crystallization initiation temperature of the polymer constituting the continuous phase, so that the crystallization temperature ranges of the two polymers do not overlap. During the casting process, the dispersed phase with the lower crystallization termination temperature preferentially crystallizes to form a uniformly dispersed microcrystalline structure, while the continuous phase with the higher crystallization initiation temperature subsequently crystallizes to form a complete continuous rigid skeleton. This crystallization sequence enables the dispersed phase microcrystals to be uniformly embedded in the continuous phase matrix, forming a "sea-island" type interpenetrating network structure with the continuous phase as the matrix and the dispersed phase as the dispersion domain. This structure is spontaneously formed during the casting process through graded crystallization, and the surface of the base film spontaneously forms a uniform uneven crystal morphology, forming an effective mechanical interlocking structure with the metal coating, which greatly improves the interfacial bonding strength between the metal coating and the base film.
[0030] In an optional embodiment, in the first and second surface layers, the mass ratio of the polymer constituting the dispersed phase to the polymer constituting the continuous phase is independently 1:(1-9), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, etc.
[0031] In an optional embodiment, the thickness of the base film is 2μm-15μm, for example, it can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc.
[0032] In an optional embodiment, the difference between the crystallization initiation temperature of the polymer constituting the continuous phase and the crystallization termination temperature of the polymer constituting the dispersed phase is ≥5°C, preferably ≥20°C.
[0033] The difference between the crystallization initiation temperature of the polymer constituting the continuous phase and the crystallization termination temperature of the polymer constituting the dispersed phase is ≥5℃, ensuring the sequential separation of the two phase structures. This facilitates the nucleation and initial growth of the dispersed phase under conditions without competition from the continuous phase, resulting in a uniform nucleus density and consistent protrusion height on the surface of the formed base film. In particular, when the difference between the crystallization initiation temperature of the polymer constituting the continuous phase and the crystallization termination temperature of the polymer constituting the dispersed phase is ≥20℃, this temperature difference is sufficient to completely eliminate any possible transitional coupling regions between the crystallization temperature zones of the two phases, fundamentally preventing grain interference and defect generation caused by co-crystallization. When the difference between the crystallization initiation temperature of the polymer constituting the continuous phase and the crystallization termination temperature of the polymer constituting the dispersed phase is <5℃ (i.e., overlapping temperature zones or excessively narrow gaps), the crystallization behavior of the two phases is prone to overlap and competition, forming a co-crystallization region. Within this region, the dispersed phase grains and the continuous phase grains interpenetrate and compress each other, leading to coarse grains, uneven size distribution, and numerous structural defects and internal stress concentration points at the grain boundaries.
[0034] In some preferred embodiments, the first and second surface layers, each comprising 100% by weight, independently include: 10%-45% of the polymer constitutes the dispersed phase, 50%-85% of the polymer constitutes the continuous phase; and optionally 1%-5wt% compatibilizer.
[0035] Among them, "10%-45%" can be, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, etc. "50%-85%" can be, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, etc.
[0036] The aforementioned content range represents a deep coupling between the hierarchical crystallization mechanism and the performance requirements of the composite current collector base film. A dispersed phase content of 10%-45% ensures the formation of sufficiently dense and isolated nucleation sites in the first step of hierarchical crystallization (preferential crystallization of the dispersed phase), provides sufficient spatial confinement effects in the second step (continuous phase crystallization), and provides sufficient anchoring structure density in the third step (secondary crystallization of the dispersed phase). A continuous phase content of 50%-85% ensures sufficient dispersion medium in the first step of hierarchical crystallization and forms a continuous load-bearing skeleton in the second step. When the dispersed phase content is below 10%, the surface anchoring site density is insufficient, resulting in too few anchoring points on the base film surface for mechanical bonding of the metal coating. Consequently, the metal coating is prone to interfacial debonding under interfacial shear forces. Furthermore, a dispersed phase content below 10% provides insufficient spatial confinement during the crystallization process of the continuous phase. The continuous phase can grow freely over a large area, forming spherulites with sizes reaching tens of micrometers. The interlamellar connections within these large spherulites are fragile and prone to brittle fracture along spherulite boundaries or interlamellar interfaces under external forces, negatively impacting the elongation at break of the base film. A continuous phase content of 50%-85% is the minimum structural requirement to ensure the formation of a continuous framework and guarantees phase morphology stability during crystallization. If the continuous phase content is below 50%, the continuous phase cannot achieve continuity in three-dimensional space, and its tensile strength and high-temperature dimensional stability will fail to meet the requirements for use in composite current collector base films.
[0037] Optionally, the compatibilizer includes maleic anhydride-grafted polyolefins, preferably including at least one of maleic anhydride-grafted polypropylene (MAH-g-PP), maleic anhydride-grafted polyethylene (MAH-g-PE), and maleic anhydride-grafted polyolefin elastomer (MAH-g-POE).
[0038] In some preferred embodiments, the polymer constituting the dispersed phase and the polymer constituting the continuous phase are selected from one of the following combinations: PET / PE, PEN / PET, PET / PBT, PTT / PBT, PPS / PBT, PBT / PE, PET / PP, PP / PE, PA / PE, PBT / POE, PEN / PP, PBT / PP, PPS / PP, PLA / PVC, PEN / PE, PPS / PE, PPS / PBT, PTT / PBT, PEEK / PA12, PEEK / PVDF, PPS / PA6, or PPS / fluoroplastics (such as PVDF). The above systems have well-matched physicochemical properties between the two phases and significantly different crystallization temperature ranges, enabling stable hierarchical crystallization while maintaining core properties such as electrolyte resistance, high and low temperature resistance, and aging resistance under lithium battery operating conditions.
[0039] In an optional embodiment, in the first and second surface layers, the polymer constituting the dispersed phase is dispersed in a microcrystalline morphology with a particle size ≤5μm, preferably ≤500 nm, more preferably ≥100 nm, and ≤500 nm. The nano / micron-scale uneven morphology formed by the protrusion of dispersed phase microcrystals from the continuous phase matrix surface in the base film is the structural basis for the physical-mechanical interlocking of the metal coating. When the dispersed phase particle size is >5μm, its protrusion height may exceed the coating thickness, and the coating cannot completely cover the protrusion tips, forming an "exposed" defect. At the same time, excessively large gaps are formed between the protrusion roots and the coating, which not only fail to provide effective anchoring but also become the initiation point of interfacial stress concentration and the channel for electrolyte penetration. The interfacial bonding between the nano-scale dispersed phase and the continuous phase is dense and free of microporous defects, making it difficult for electrolyte to preferentially penetrate along the interface, thus endowing the base film with corrosion resistance far superior to that of micron-scale blends.
[0040] The dispersed phase is formed by crystallizing the polymer constituting the dispersed phase; the continuous phase is formed by crystallizing the polymer constituting the continuous phase.
[0041] In some preferred embodiments, the base film further includes a core layer, wherein the first surface layer, the core layer, and the second surface layer are stacked sequentially; the thickness of the first surface layer and the thickness of the second surface layer each independently account for 15%-30% of the thickness of the core layer.
[0042] In some preferred embodiments, the polymer constituting the dispersed phase is PE, the polymer constituting the continuous phase is PP, and the core layer is PP or PE; in other preferred embodiments, the polymer constituting the dispersed phase is PET, the polymer constituting the continuous phase is PEN, and the core layer is PBT or PEN.
[0043] like Figure 1 As shown, a second aspect of the present invention provides a method for preparing a base film, comprising: (A) The polymer constituting the dispersed phase of the first surface layer is mixed with the polymer constituting the continuous phase and then melted to obtain the melt of the first surface layer; (B) The polymer constituting the dispersed phase of the second surface layer is mixed with the polymer constituting the continuous phase and then melted to obtain the melt of the second surface layer; (C) The melt including the first surface layer and the melt including the second surface layer are co-extruded and then subjected to casting and stretching processes to obtain the base film; In the casting process, the crystallization of the polymer constituting the dispersed phase and the crystallization of the polymer constituting the continuous phase are carried out sequentially. The casting process includes: (a) Cooling to the crystallization temperature range of the polymer constituting the dispersed phase, so that the polymer constituting the dispersed phase is at least partially crystallized; (b) Heating to the crystallization temperature range of the polymer constituting the continuous phase, causing the polymer constituting the continuous phase to crystallize; (c) Cool to the crystallization temperature range of the polymer constituting the dispersed phase, so that the polymer constituting the dispersed phase can be fully crystallized.
[0044] The forming mechanism of the base film provided by this invention is as follows: First, during the casting process of the blended melt, the temperature is rapidly reduced to the crystallization temperature range of the dispersed phase, which is relatively low. This promotes the preferential formation of crystal nuclei and grain growth in at least part of the dispersed phase, forming initial crystal nuclei protruding from the melt surface and uniformly forming a fine and dispersed microcrystalline structure of the dispersed phase. Subsequently, the temperature is increased to the crystallization temperature range of the dispersed phase, which is relatively high. The continuous phase molecular chains encapsulate and crystallize around these protruding dispersed phase crystal nuclei. Finally, the temperature is reduced again to the crystallization temperature range of the dispersed phase, which promotes secondary crystallization of the dispersed phase, further densifying and "expanding" its grains. This results in the spontaneous formation of nail-head-shaped or mushroom-shaped mechanical interlocking structures (i.e., nano-interlocking morphology) on the surface of the base film. The grains on the surface of the base film are densely and uniformly arranged, free of pore defects, and have extremely low internal stress, significantly improving structural stability. This native micro-rough structure requires no subsequent modification and can be directly integrated with copper and aluminum metal nuclei deposited by magnetron sputtering to construct a physically anchored bonding structure. This significantly enhances the interfacial bonding strength between the base film and the metal coating, completely solving the core problem of weak native interfacial bonding of PP and PET substrates.
[0045] Specifically, in terms of the segmented constant temperature cooling molding process parameters, this invention adopts a three-stage precise temperature control crystallization process to achieve time-sequential and differentiated controllable crystallization of the dispersed phase and the continuous phase. The first stage is the rapid cooling crystallization stage, with a cooling rate set at 50℃ / min-100℃ / min. After entering the dispersed phase crystallization range, the temperature is held constant for 30s-120s to ensure preferential and uniform nucleation and growth of the dispersed phase in the low-temperature region, forming a diffuse and uniform microcrystalline structure. The second stage is the temperature-controlled heating crystallization stage, with a heating rate set at 10℃ / min-30℃ / min. The temperature is precisely raised to the continuous phase crystallization temperature range and held constant for 60-600s, providing sufficient isothermal crystallization time for the continuous phase polymer chain segments to fully and regularly arrange, constructing a continuous, dense, and rigid base film framework, and ensuring the overall mechanical strength and structural integrity of the film. The third stage is the slow shaping and cooling stage, with a controlled cooling rate of 5℃ / min-30℃ / min to cool to the dispersed phase crystallization temperature range and held constant for 30s-120s. This stage adapts to the uniform secondary crystallization of the dispersed phase, further optimizing the nano-uneven microstructure of the base film surface and improving the interfacial anchoring adaptability.
[0046] The crystallization optimization scheme provided by this invention can directly replace the traditional post-remedial modification processes such as corona treatment, plasma activation, and acrylic primer coating. It avoids the inherent defects of traditional modification processes, such as poor timeliness, insufficient mass production consistency, weak resistance to electrolyte corrosion, and easy delamination failure during long-term service. While reducing production processes and controlling mass production costs, it achieves a synergistic improvement in multiple properties, including the mechanical properties of the base film, interfacial bonding force, and electrolyte stability.
[0047] The base film and preparation process provided by this invention have the following advantages; 1. Excellent dimensional and high-temperature stability: The base film surface layer is constructed with two polymers with non-overlapping crystallization intervals and a specific hierarchical crystallization process to build a three-dimensional continuous crystal skeleton, which improves the mechanical properties of the base film and effectively reduces the thermal shrinkage rate of the base film. It is compatible with magnetron sputtering and electroplating processes with full heating. The composite current collector has high dimensional consistency of the whole roll and improves the mass production yield. 2. Electrolyte corrosion resistance suitable for lithium battery operating conditions: The dense and closed grain boundaries of hierarchical crystallization block the electrolyte penetration channels. After long-term immersion in electrolyte, the coating adhesion decreases by less than 10%, making it suitable for long-term cyclic use of energy storage and power lithium batteries. 3. Significantly improved coating adhesion: Non-overlapping zones achieve complete time-sequential crystallization, resulting in a uniform nano-intercalated crystal structure on the base film surface. This enhances the mechanical interlocking strength of the metal coating, ensuring no delamination or copper loss after thousands of charge-discharge cycles. It eliminates the need for strong plasma activation and adhesive base coating, simplifying mass production processes. 4. Controllable phase structure suitable for mass production: There is no problem of two-phase crystal coexistence and extrusion. The dispersed phase can be stably controlled with a particle size of 500nm and below. There are no agglomerated large particles. The base film has uniform light transmission and no crystal point defects on the surface. It is suitable for the production of ultra-thin 2-6μm lithium battery-specific base films. 5. Low-cost and highly adaptable process: Graded crystallization can be achieved simply by selecting the raw material crystallization range and segmented temperature control cooling. No high-content modifying agents are required. It is fully compatible with existing biaxially oriented composite current collector base film production lines, and the modification cost is extremely low.
[0048] In some preferred embodiments, the preparation method satisfies one or more of the following conditions: (1) In step (a), the cooling rate is 50℃ / min-100℃ / min, for example, it can be 50℃ / min, 75℃ / min, 100℃ / min, etc., and the temperature is kept constant for 30-120s within the crystallization temperature range of the polymer constituting the dispersed phase, for example, it can be 30s, 75s, 120s, etc. (2) In step (b), the heating rate is 10℃ / min-30℃ / min, for example, it can be 10℃ / min, 20℃ / min, 30℃ / min, etc. After heating, the temperature is kept constant for 60-600s within the crystallization temperature range of the polymer constituting the continuous phase, for example, it can be 60s, 100s, 200s, 300s, 400s, 500s, 600s, etc. (3) In step (c), the cooling rate is 5℃ / min-30℃ / min, for example, it can be 5℃ / min, 10℃ / min, 15℃ / min, 20℃ / min, 25℃ / min, 30℃ / min, etc. After the heating, the temperature is kept constant for 30-120s within the crystallization temperature range of the polymer constituting the continuous phase, for example, it can be 30s, 60s, 90s, 120s, etc.
[0049] A third aspect of the present invention provides a composite current collector, the composite current collector comprising the base film described above or the base film prepared by the preparation method described above.
[0050] A fourth aspect of the present invention provides an electrode comprising the aforementioned composite current collector.
[0051] A fifth aspect of the present invention provides an electrochemical device comprising the aforementioned electrode.
[0052] The present invention will be further illustrated by the following examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.
[0053] Example 1 This embodiment provides a base film, the preparation process of which is as follows: (1) Raw material preparation Weigh the following components by mass percentage: The polymer constituting the dispersed phase is PE, with a crystallization initiation temperature of 90℃ and a crystallization termination temperature of 125℃. The polymer constituting the continuous phase is PP, with a crystallization initiation temperature of 130℃ and a crystallization termination temperature of 155℃. Compatibilizer: Maleic anhydride-grafted polypropylene (PP-g-MAH); The raw materials and their mass fractions for the first surface layer are: 30 wt% PE, 65 wt% PP, and 5 wt% PP-g-MAH. The raw materials and their mass fractions for the second surface layer are: 30% PE, 65% PP, and 5% PP-g-MAH; The core layer is made of PP.
[0054] (2) Melt blending The raw materials for the first surface layer are melt-blended at 200°C in a certain proportion to obtain the first surface layer melt. The raw materials for the second surface layer are melt-blended at 200°C in a certain proportion to obtain the second surface layer melt. The core layer material is melted at 200°C to obtain the core layer melt.
[0055] (3) The melt including the first surface layer, the core layer melt and the second surface layer melt are co-extruded and then sequentially subjected to casting and stretching processes to obtain the base film; In the casting process, the crystallization of the polymer constituting the dispersed phase and the crystallization of the polymer constituting the continuous phase are carried out sequentially. The casting process includes: (a) First stage of cooling and crystallization: After the melt is extruded, it is cooled to 110°C to crystallize the dispersed phase; wherein, the cooling rate is 75°C / min, and the temperature is kept constant for 75s within the crystallization temperature range of the polymer constituting the dispersed phase. (b) Second stage of heating and crystallization: The temperature is then raised to 145°C to carry out the crystallization of the continuous phase; wherein, the cooling rate is 75°C / min, and after heating, the temperature is kept constant for 330 s within the crystallization temperature range of the polymer constituting the continuous phase. (c) Third stage slow setting: Then cool down to 110°C to carry out secondary crystallization of the dispersed phase; wherein, the cooling rate is 18°C / min, and the temperature is kept constant for 75s within the crystallization temperature range of the polymer constituting the dispersed phase.
[0056] Stretching process: Stretching temperature: 150℃, longitudinal stretching ratio: 7 times, transverse stretching ratio: 8.6 times; the total thickness of the base film is 6 micrometers, and the thickness of the first surface layer and the second surface layer each account for 20% of the total thickness of the base film.
[0057] Example 2 This embodiment provides a base film, which differs from Embodiment 1 in that the raw materials and their mass fractions for the first and second surface layers are both: 10% PE, 85% PP, and 5% PP-g-MAH.
[0058] Example 3 This embodiment provides a base film, which differs from Embodiment 1 in that the mass fraction of each component in the first and second surface layers is 45% PE, 50% PP, and 5% PP-g-MAH.
[0059] Example 4 This embodiment provides a base film, which differs from Embodiment 1 in that: In step (a), the cooling rate is 50 °C / min, and the temperature is kept constant for 120 s within the crystallization temperature range of the polymer constituting the dispersed phase. In step (b), the heating rate is 30℃ / min, and after heating, the temperature is kept constant for 60 s within the crystallization temperature range of the polymer that constitutes the continuous phase. In step (c), the cooling rate is 5°C / min, and the temperature is kept constant for 120s within the crystallization temperature range of the polymer constituting the dispersed phase.
[0060] Example 5 This embodiment provides a base film, which differs from Embodiment 1 in that: In step (a), the cooling rate is 100℃ / min, and the temperature is kept constant for 30s within the crystallization temperature range of the polymer constituting the dispersed phase. In step (b), the heating rate is 10℃ / min, and after heating, the temperature is kept constant for 600 s within the crystallization temperature range of the polymer that constitutes the continuous phase. In step (c), the cooling rate is 30°C / min, and the temperature is held constant for 30 seconds within the crystallization temperature range of the polymer constituting the dispersed phase.
[0061] Example 6 This embodiment provides a base film, which differs from Embodiment 1 in that: The polymer PBT constituting the dispersed phase has a crystallization initiation temperature of 140℃ and a crystallization termination temperature of 160℃. Polymer constituting the continuous phase: PEN, with a crystallization initiation temperature of 180℃ and a crystallization termination temperature of 230℃; The core layer is PBT.
[0062] The casting process includes: (a) First stage of cooling and crystallization: After the melt is extruded, it is cooled to 150°C to crystallize the dispersed phase; wherein, the cooling rate is 75°C / min, and the temperature is kept constant for 75s within the crystallization temperature range of the polymer constituting the dispersed phase. (b) Second stage of heating and crystallization: The temperature is then raised to 200°C to carry out the crystallization of the continuous phase; wherein the cooling rate is 75°C / min, and after heating, the temperature is kept constant for 330 s within the crystallization temperature range of the polymer constituting the continuous phase. (c) Third stage slow setting: Then cool down to 150°C to carry out secondary crystallization of the dispersed phase; wherein, the cooling rate is 18°C / min, and the temperature is kept constant for 75s within the crystallization temperature range of the polymer constituting the dispersed phase.
[0063] Melt co-extrusion temperature: 310℃, stretching temperature: 130℃, longitudinal stretching: 1.2 times; transverse stretching: 2.6 times.
[0064] Example 7 This embodiment provides a two-phase polymer blend base film, which differs from Embodiment 1 in that: step (a) uses slow cooling at a rate of 18°C / min; and step (c) uses rapid cooling at a rate of 75°C / min.
[0065] Comparative Example 1 This comparative example provides a base film, which differs from Example 6 in that: in step (3), the temperature is gradually reduced in the casting process at a rate of 20°C / min. The temperature is first reduced to the crystallization temperature range of the continuous phase with a higher crystallization temperature range and held for 330s, and then further reduced to the crystallization temperature range of the dispersed phase with a lower crystallization temperature range and held for 150s.
[0066] Comparative Example 2 This comparative example provides a base film, which differs from Example 1 in that: in step (3), the temperature is gradually reduced in the casting process at a rate of 20°C / min. The temperature is first reduced to the crystallization temperature range of the continuous phase with a higher crystallization temperature range and held for 330s, and then further reduced to the crystallization temperature range of the dispersed phase with a lower crystallization temperature range and held for 150s.
[0067] Comparative Example 3 This comparative example provides a base film that differs from Example 1 in that the dispersed phase secondary crystallization in step (c) is absent in step (3).
[0068] Test example: Composite copper foils were prepared using the base films obtained in the above embodiments and comparative examples. The process involved preparing a copper seed layer on the surface of the base film using magnetron sputtering, controlling the seed layer thickness to be 40 nm; followed by electroplating with a current density of 2.5 A / dm³.2 Electroplating for 120 seconds resulted in a copper layer thickness of 1.2 μm on one side.
[0069] Test method: Mechanical property testing: The cut sample is held stably and vertically in the upper and lower clamps. A preload of 0.1N is applied at a rate of 10 mm / min, and then the speed is automatically switched to 50 mm / min for tensile testing until the sample breaks. The tensile strength is the strength value when the metal layer and the base film layer of the composite current collector break simultaneously.
[0070] Peel strength: The metal coating and the base film are pre-separated at one end of the composite current collector sample to form an initial peel opening. The sample is then clamped in the upper and lower fixtures of the universal testing machine to form a 180° peel angle. Tensile peeling is performed at a constant speed (usually 50 mm / min).
[0071] Base film heat shrinkage test: For PP / PE system: bake at 120℃ for 30 min; For PEN / PBT system: bake at 150℃ for 30 min.
[0072] Table 1
[0073] The data in the table show that, compared to the comparative example, the present invention achieves a significant synergistic improvement in interfacial bonding force (peel strength), mechanical properties (tensile strength), and dimensional stability (thermal shrinkage rate). First, the data in Table 1 confirms that the dispersed phase preferentially crystallizes and expands during the secondary crystallization stage, effectively forming a nail-head-shaped mechanical interlocking structure; if the continuous phase crystallizes first, the dispersed phase's embedding depth is insufficient, failing to provide effective anchoring. Second, the present invention eliminates the competition between the two phases for crystallization and internal stress concentration through sequential hierarchical crystallization, and the dense grain boundaries effectively resist high-temperature molecular chain disorientation; the comparative example, due to co-crystallization, results in coarse grains and uneven internal stress distribution, leading to severe shrinkage due to stress release at high temperatures.
[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A base film, characterized in that, The base film includes at least a first surface layer and a second surface layer, each of which independently includes at least a polymer constituting a dispersed phase and a polymer constituting a continuous phase. Wherein, the polymer constituting the continuous phase at least partially encapsulates the polymer constituting the dispersed phase; the crystallization termination temperature of the polymer constituting the dispersed phase is lower than the crystallization initiation temperature of the polymer constituting the continuous phase; the preparation of the base film includes a casting process, and during the casting process, the polymer constituting the dispersed phase crystallizes at least partially before the polymer constituting the continuous phase.
2. The base film according to claim 1, characterized in that, In both the first and second surface layers, the mass ratio of the polymer constituting the dispersed phase to the polymer constituting the continuous phase is independently 1:(1-9); and / or, The thickness of the base film is 2μm-15μm.
3. The base film according to claim 1, characterized in that, In the first and second surface layers, the difference between the crystallization initiation temperature of the polymer constituting the continuous phase and the crystallization termination temperature of the polymer constituting the dispersed phase is ≥5°C, preferably ≥20°C; and / or, In the first and second surface layers, the crystalline particle size of the polymer constituting the dispersed phase is ≤5μm, preferably ≤500 nm.
4. The base film according to claim 1, characterized in that, Based on 100% by mass, the first and second surface layers each independently comprise 10%-45% of the polymer constituting the dispersed phase and 50%-85% of the polymer constituting the continuous phase.
5. The base film according to claim 1, characterized in that, The polymer constituting the dispersed phase and the polymer constituting the continuous phase are selected from one of the following combinations: PET / PE, PEN / PET, PET / PBT, PTT / PBT, PPS / PBT, PBT / PE, PET / PP, PP / PE, PA / PE, PBT / POE, PEN / PP, PBT / PP, PPS / PP, PLA / PVC, PEN / PE, PPS / PE, PPS / PBT, PTT / PBT, PEEK / PA12, PEEK / PVDF, PPS / PA6 or PPS / fluoroplastics; and / or, Based on 100% by weight, the first surface layer and the second surface layer also independently include 1%-5% compatibilizer; Optionally, the compatibilizer includes maleic anhydride-grafted polyolefins, preferably including at least one of maleic anhydride-grafted polypropylene, maleic anhydride-grafted polyethylene, and maleic anhydride-grafted polyolefin elastomers.
6. The method for preparing the base film according to any one of claims 1-4, characterized in that, include: (A) The polymer constituting the dispersed phase of the first surface layer is mixed with the polymer constituting the continuous phase and then melted to obtain the melt of the first surface layer; (B) The polymer constituting the dispersed phase of the second surface layer is mixed with the polymer constituting the continuous phase and then melted to obtain the melt of the second surface layer; (C) The melt including the first surface layer and the melt including the second surface layer are co-extruded and then subjected to casting and stretching processes to obtain the base film; In the casting process, the crystallization of the polymer constituting the dispersed phase and the crystallization of the polymer constituting the continuous phase are carried out sequentially. The casting process includes: (a) Cooling to the crystallization temperature range of the polymer constituting the dispersed phase, so that the polymer constituting the dispersed phase is at least partially crystallized; (b) Heating to the crystallization temperature range of the polymer constituting the continuous phase, causing the polymer constituting the continuous phase to crystallize; (c) Cool to the crystallization temperature range of the polymer constituting the dispersed phase, so that the polymer constituting the dispersed phase can be fully crystallized.
7. The preparation method according to claim 6, characterized in that, One or more of the following conditions must be met: (1) In step (a), the cooling rate is 50℃ / min-100℃ / min, and the temperature is kept constant for 30s-120s within the crystallization temperature range of the polymer constituting the dispersed phase. (2) In step (b), the heating rate is 10℃ / min-30℃ / min, and after heating, the temperature is kept constant for 60s-600s within the crystallization temperature range of the polymer constituting the continuous phase. (3) In step (c), the cooling rate is 5℃ / min-30℃ / min, and after cooling, the temperature is kept constant for 30s-120s within the crystallization temperature range of the polymer constituting the dispersed phase.
8. A composite current collector, characterized in that, The composite current collector includes the base film according to any one of claims 1 to 5 or the base film prepared by the preparation method according to any one of claims 6 to 7.
9. An electrode sheet, characterized in that, The electrode includes the composite current collector as described in claim 8.
10. An electrochemical device, characterized in that, The electrochemical device includes the electrode as described in claim 9.
